Evaluation of Bevacizumab in Advanced Small Bowel Adenocarcinoma. - Aydin, Dincer; Sendur, Mehmet Ali; Kefeli, Umut; Ustaalioglu, Basak Bala; Aydin, Ozhan; Yildirim, Emre; Isik, Deniz; Ozcelik, Melike; Surmeli, Heves; Oyman, Abdilkerim; Isik, Selver; Sener, Nur; et al. (My University, 2017)
Small bowel adenocarcinomas (SBAs) are rarely seen tumors. Data regarding the use of chemotherapy together with bevacizumab in patients with advanced SBA are lacking. The aim of this study was the evaluation of treatment with bevacizumab in advanced SBA.

Twenty-eight patients from 5 centers with a diagnosis of advanced SBA who received first-line treatments with modified FOLFOX6 (mFOLFOX6; oxaliplatin, leucovorin, and 5-fluorouracil) and FOLFIRI (leucovorin, 5-fluorouracil, and irinotecan) chemotherapy regimens were involved in the study. All patients were divided into 2 groups; those who received bevacizumab together with these chemotherapy regimens (Chemo+Bev group) and those who did not receive bevacizumab (Chemo group).

The median progression-free survival (PFS) and overall survival (OS) times of all population were 8.7 months and 16.9 months, respectively. The overall response rate was 43.7% in the Chemo group and 58.3% in the Chemo+Bev group. The median PFSs in the Chemo and Chemo+Bev groups were found to be 7.7 months and 9.6 months, respectively, and the median OSs were 14.8 months and 18.5 months, respectively. There was not a significant difference between the groups in terms of overall response rate, PFS, and OS.

Although there was no significant difference in any of the outcomes, use of bevacizumab together with chemotherapy is a more effective treatment approach compared with chemotherapy alone, and it does not cause an excess of significant toxicity.
Keywords: Adenocarcinoma; Advanced; Bevacizumab; Bowel; Small